Investigation of penetrator defect formation during high frequency induction welding in pipeline steels - Sofras Christos (EDP Sciences, 2021)
The aim of this study is to investigate the formation of oxide defects known as penetrators during high frequency induction welding process of high strength low alloy pipeline steels and to correlate their formation with the steel chemical composition. Penetrators formed during the welding process can be detrimental for the impact properties of the weld seam. For this purpose, three different samples, with different chemical compositions, were intentionally produced with penetrator-type oxides and investigated. In order to characterize the oxide defect and correlate their formation with the chemical composition of the steel, optical microscopy and scanning electron microscopy paired with energy dispersive spectroscopy were employed. In addition, thermodynamic calculations were performed in order to examine whether the chemical composition of pipeline steels is prone to oxide formation. The results showed that oxides with pancake type morphology were found alongside the fusion zone of the samples. They mainly consisted of manganese and silicon. First findings on the the Mn/Si ratio showed that the lower ratio is less susceptible to oxide formation.